Development of diffuse large B‐cell lymphoma during dupilumab treatment in a patient with atopic dermatitis: A case report - Hideaki Uchida; Masahiro Kamata; Mayumi Nagata; Saki Fukaya; Kotaro Hayashi; Atsuko Fukuyasu; Takamitsu Tanaka; Takeko Ishikawa; Takamitsu Ohnishi; Kenjiro Mitsuhashi; Yayoi Tada (Journal of Cutaneous Immunology and Allergy, 2021)
This case report describes a 44‐year‐old male patient with atopic dermatitis who developed malignant lymphoma (diffuse large B‐cell lymphoma) during the dupilumab treatment.